Penerapan Pasal Enam Kode Etik Jurnalistik Pada Wartawan Surat Kabar Harian Metro Siantar - Sabilla, Madika; Budiman, Dwi Aji; Sari, Eka Vuspa (Tuturlogi: Journal of Southeast Asian Communication, 2023)
This research aims to find out the understanding and practice of applying article six of the journalistic code of ethics to journalists for the daily newspaper Metro Siantar, referring to the Theory of Social Responsibility Of The Press. The method used in this research is descriptive qualitative by collecting complete research data through interviews, observations, and documentation studies. The results of research conclude that journalists Metro Siantar daily fully understands article 6 of the journalistic code of ethics related to professional abuse and accepting bribes among journalists.The application of article 6 of this journalistic code of ethics as a reference and benchmark for the professionalism of journalists of Metro Siantar daily in carrying out their duties at l wish. A journalist must firmly reject attempts to give bribes and if there are journalists from the Metro Siantar daily who still accept the gift, it will be returned to the source through the editor-in-chief. Metro Siantar daily provides briefing to its journalists in the form of internal and external training, appeals, and monthly evaluations to remind and re-explain the application of the journalistic code of ethics even though Metro Siantar daily journalists already know about it. The implication of this research is for Metro Siantar daily journalists to keep upholding professionalism and morality in carrying out the journalistic profession.